2012
DOI: 10.7764/laje.49.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Does corruption affect economic growth?

Abstract: Using panel data from the International Country Risk Guide corruption index, institutional quality and political stability indices and several state variables for developed and developing countries, this paper explores the linear quadratic empirical relationship between corruption and economic growth. Empirical literature has shown a linear relationship between corruption and economic growth but hasn't dif ferentiated between growthenhancing and growth-reducing levels of corruption. An analysis based on the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 26 publications
4
72
0
3
Order By: Relevance
“…It exerts negative effects on both economic and social spheres (Aguilera and Vadera 2008;Ahmad et al 2012;Davis and Ruhe 2003;Gray and Kaufman 1998;Mauro 1995;Mo 2001;Swaleheen 2011). Corruption also has negative consequences in the political domain, such as reduced interest in political participation, impaired democracy, and social inequality (Judge et al 2011).…”
Section: Corruption Perception and Political Participationmentioning
confidence: 98%
“…It exerts negative effects on both economic and social spheres (Aguilera and Vadera 2008;Ahmad et al 2012;Davis and Ruhe 2003;Gray and Kaufman 1998;Mauro 1995;Mo 2001;Swaleheen 2011). Corruption also has negative consequences in the political domain, such as reduced interest in political participation, impaired democracy, and social inequality (Judge et al 2011).…”
Section: Corruption Perception and Political Participationmentioning
confidence: 98%
“…Empirical literature, for instance, the works of Mauro and Carmeci (2007), Nageri, Gunu and Falilat (2013) and Ekundayo et al (2013) have consistently reported a negative linear relationship between economic growth and economic crimes except the works of Ahmad et al (2012) and Aidt, Dutta and Sena (2008) who found non-linear relationship between economic growth and economics crimes in a panel of countries. It is, however, not certain if a non-linear relationship exists between economic crimes and economic growth in Nigeria as no empirical investigation on the relationship between economic growth and economic crimes have come to this conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, corruption perception index is just the perception of individuals with regard to corruption and this perception is largely subjective with minimal time points. Ahmad et al (2012) using panel data from 1984 to 2009 for 71 developed and developing countries, with corruption index, corruption squared, bureaucratic efficiency index, political stability index, institutional efficiency index, risk to investment index etc while employing generalized methods of moments estimation (GMM) find that decrease in corruption raises economic growth rate in an inverted U-shaped way. Aidt et al (2008), in an empirical study on Governance Regimes, Corruption and Growth: Theory and Evidence in a panel data analysis using voice and accountability index, corruption index and gdp as variables found a non-linear relationship between corruption and growth and therefore concluded that there is no relationship between corruption and growth in countries with low-quality political institutions.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations